(4x-5)(x+2)=0

Simple and best practice solution for (4x-5)(x+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-5)(x+2)=0 equation:


Simplifying
(4x + -5)(x + 2) = 0

Reorder the terms:
(-5 + 4x)(x + 2) = 0

Reorder the terms:
(-5 + 4x)(2 + x) = 0

Multiply (-5 + 4x) * (2 + x)
(-5(2 + x) + 4x * (2 + x)) = 0
((2 * -5 + x * -5) + 4x * (2 + x)) = 0
((-10 + -5x) + 4x * (2 + x)) = 0
(-10 + -5x + (2 * 4x + x * 4x)) = 0
(-10 + -5x + (8x + 4x2)) = 0

Combine like terms: -5x + 8x = 3x
(-10 + 3x + 4x2) = 0

Solving
-10 + 3x + 4x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-2 + -1x)(5 + -4x) = 0

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25

Solution

x = {-2, 1.25}

See similar equations:

| iz^2+3z+4i=0 | | 3x+7=2(3+4) | | 7(x-2)-4=5x+20 | | 2x+3y=86 | | 10x-2x+20=4(2x+5) | | 6.40(9)+7.28p=6.40(9+p) | | 51x-12x+(56-4)=94x+34 | | Z^3+3Z+5=0 | | 6.40(9)-7.28p=6.40(9+p) | | (4x-5)(x+2)=12 | | 14x+82=86x-2 | | 10x+25=5x-10 | | (X-12)+(2x+18)=180 | | 4x+2x+6x+2+4+6=8+2+10 | | 3x+x+x=180 | | (x-2)/4=1,25x-x | | 0.90(8)+1.04p=0.98(8+p) | | -4x+14=x-1 | | 2/3(x-4)=5/4-7x | | 5(2x-4)+10=5x+35 | | 5+2r=2r+6 | | 0.98(8)-1.04p=0.98(8+p) | | 3(2x-2)-9=-x+34 | | 7a-3=3+6n | | 30=5(x+2) | | 0.98(8)+1.04p=0.98(8+p) | | 3(2x-1)-3=48 | | 2(x-1)=-x+16 | | -x-9=3x+11 | | -x+47=4(x-2) | | -7x-3x+2=-8 | | 2x^2+4y^2-4x-24y+36=0 |

Equations solver categories